Development and Validation of Visualisation Ability Test for Technical Drawing Students Using Rasch Models - Marji, Mohd Salehudin; Mustaamal, Aede Hatib; Che Derasid, Nor Aisyah; Leong, Ting Chee (Journal of Technical Education and Training, 2026)
This study aimed to develop a visualization ability test for technical drawing students and to provide preliminary evidence of its validity and reliability using the Rasch model.. The main problem is the lack of a specific measuring tool to assess students’ visualization abilities in the context of technical drawing in Malaysia. The study employed a development approach, involving four experts in technical drawing, engineering, and architecture, as well as 34 Form 4 Grafik Komunikasi Teknikal students from two secondary schools in Johor as the sample. Expert validation showed content validity, with an overall Fleiss’ Kappa of 0.85, while Rasch analysis indicated good item reliability (0.84) and a Cronbach’s Alpha of 0.77. The analysis showed that the instrument consistently and significantly distinguished different levels of students’ visualization ability. This study provides preliminary evidence that the developed test has acceptable validity and reliability for assessing visualization ability in technical drawing learning. Recommendations are offered for further research with larger samples and for integrating technology to improve the application and generalizability of results.